OBSTACLES OF IMPLEMENTING STRATEGIC PLANNING FROM SECONDARY SCHOOL PRINCIPALS’ PERSPECTIVES IN KHARTOUM STATE - Bannaga Taha Al-Zubair; El-Zain El-Khalefa El-khder (MANAGERE : Indonesian Journal of Educational Management, 2021)
This study aimed at identifying the main obstacles that face the implementation of strategic planning from secondary school principals’ perspectives in Khartoum State. To meet the study purpose, the descriptive research method was used. The study population consists of all secondary school principals in Omdurman locality amount 220. Out of the study population, 110 principals were selected through a random sample technique. The data were collected using a designed a questionnaire by the researchers. To analyse the collected data, the researchers used the Chi2 test through the Statistical Package of Social Sciences (SPSS). The school principals face difficulties in analysing the points of strength, weakness opportunities, and threats of their schools as they lack the basic scientific foundations and knowledge of strategic planning. The school principals encounter difficulties and problems when they try introduce the strategic planning of their schools because they lack the basic required skills and competencies regarding the implementation of strategic planning processes.  The study recommended that the principals’ skills should be developed to meet the strategic planning requirements. Besides, more attention needs to be given to the obstacles that hinder the implementation of strategic planning processes in the future studies